A Case of Mistaken Identity? Latent Profiles in Vocational Interests. (February 2015) - McLarnon, Matthew J. W.; Carswell, Julie J.; Schneider, Travis J.
Vocational interest surveys have traditionally employed a typology (i.e., the Realistic, Investigative, Artistic, Social, Enterprising, and Conventional [RIASEC] model) to distinguish individuals. Within this framework, respondents are identified as representing various types of people based on their interests in work-related activities. However, much of the existing literature on vocational interest testing has focused almost exclusively on traditional variable-centered approaches to understanding the nomological network around vocational interest variables. Therefore, the focus of the current article is an application of a person-centered approach, latent profile analysis (LPA). Using LPA, we found evidence of eight qualitatively and quantitatively distinct subgroups or types of individuals differentiated on the basis of interests in the RIASEC variables. Further, across the five-factor model and Dark Triad personality variables, minor, yet theoretically sound, differences across the eight vocational interest subgroups were found. Theoretical and practical implications are discussed.